Drinking water: problems related to water supply in Bahía Blanca, Argentina - Echenique, Ricardo Omar (2006)
In April 2000, alterations in drinking water quality, such as turbidity and odors similar to those of organochloride pesticides, were detected at Bahía Blanca (Argentina). This fact was associated to reports of dermic reactions and respiratory problems in the population. Samples drawn from Paso de las Piedras reservoir, two water treatment plants of at inlet and outlet points and at several particular houses were analyzed. Total phytoplankton in the reservoir varied between 49440 and 84832 cells.ml-1, while dominant species was, Anabaena circinalis. Efficiency to remove microorganisms (ER) by the treatment plants considering cell number of total phytoplankton was analyzed. Bacteriological analysis, qualitative and quantitative studies of phytoplankton, pesticides, THM (trihalomethanes) and BTEX (benzene, toluene, ethylbenzene and xylene) analysis were carried out in samples of domestic supply and in the treatment plants. Even though samples were bacteriological potable, Anabaena circinalis and Microcystis aeruginosa algae were found at high concentrations in some cases. No pesticides were detected. THM and BTEX were below guideline values into recommendations for drinking water. Geosmin was responsible for detected odors. Besides, Copaene, another volatile metabolite, which on account in its structure could be considered a Geosmin precursor, was also detected. In Argentina, this was the first report of Cyanobacteria presence in drinking water.